2006
DOI: 10.1063/1.2393157
|View full text |Cite
|
Sign up to set email alerts
|

New experimental device for infrared spectral directional emissivity measurements in a controlled environment

Abstract: A new experimental device for infrared spectral directional emissivity measurements in a controlled atmosphere is presented. The sample holder, which permits to measure spectral directional emissivity up to 1050K, is placed inside a stainless steel sample chamber that can be evacuated or filled with different gases. The signal detection is carried out by means of a Fourier transform infrared spectrometer. The experimental results focus on the capability of the device to perform emissivity measurements as a fun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
87
1
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 155 publications
(92 citation statements)
references
References 30 publications
2
87
1
2
Order By: Relevance
“…8), 10) and 11). As pointed out above, obvious oscillations of normal spectral emissivity appears only at the first several min from the heating start in this work, whereas those reported in the literature 2,[8][9][10][11]14) appeared at very different heating times, typically from several seconds to an hour in the oxidizing surroundings.…”
Section: Strong Oscillation Of the Normal Spectral Emissivitycontrasting
confidence: 50%
See 3 more Smart Citations
“…8), 10) and 11). As pointed out above, obvious oscillations of normal spectral emissivity appears only at the first several min from the heating start in this work, whereas those reported in the literature 2,[8][9][10][11]14) appeared at very different heating times, typically from several seconds to an hour in the oxidizing surroundings.…”
Section: Strong Oscillation Of the Normal Spectral Emissivitycontrasting
confidence: 50%
“…At 1.5 μm and 873 K, typically, such strong oscillation occurs at about 800-second heating time from the heating start. Campo et al 10) observed a number of weak oscillations over the wavelengths ranging from 1.28 to 25 μm at seven different heating times. Wen 11,14) observed few oscillations during the first-hour heating time.…”
Section: Strong Oscillation Of the Normal Spectral Emissivitymentioning
confidence: 99%
See 2 more Smart Citations
“…또한 동일 물질이라 하더라도 표면의 산화된 정도나 거칠기에 따라 복 사율은 다르게 측정되며, [3,4] 측정에 필요한 여러 장치들에 의 한 위상차, [5,6] 검출기의 비 선형성, [7] 대기 복사의 영향, 그리 [8] 과 radiometric 방법이 있으며, radiometric 방법에는 direct 방법 [9] 과 indirect 방법 [10] 이 있다. 최근에는 분광 복사율 측정을 위하여 퓨리에 변환 적외선 분광기(FT-IR)를 이용한 direct 방법 [1][2][3][4][5][6]11] 이 주로 사용되고 있으며, 그 중 실험 장치의 교정과 대기 복사의 보정에 효과적인 two-temperature 방법 [5,6,11] 이 물질의 분광 복사율을 측정에 주로 이용되고 있다. 본 논문에서는 퓨리에 변환 적외선 분광기(FT-IR)를 이용 한 적외선 분광 복사율 측정 장치를 기술하고, 물질의 수직 분광 복사율 및 표면 상태에 따른 복사율 변화를 측정하였 다.…”
Section: 서 론unclassified